Habitat’s para um empreendedorismo sustentável: estudo de ferramentas para potencializar práticas inovativas - Labiak Junior, Silvestre (2004)
This research analizes how social and environmental issues are treated by managers of habitats of entrepreneurship in the State of Paraná, also looking if they have knowledge of sustainable management tools and how these concepts have been transfered to incubated entrepreneurs. In order to have a better understanding of these issues, to define technology, technological education, sustainability and, entrepreneurship. It is also demonstrated at which standart entrepreneurship is practiced throughout Brazil and in the State of Paraná; through the description of the services offered by the habitats. In order to support future sustainable clusters new sustainable management tools are presented, such as: Ecological Management, The Natural Step and, ZERI (Zero Emission Research Initiative), which could introduce sustainable culture among entrepreneurs located in incubators and technological parks. A field research was done amongst fourteen managers of incubators and technological parks out of twenty-three located in the State of Paraná. Results show that very little has been done by the managers in order to disseminate sustainable management in incubated companies. By understanding that this kind of the environment business is essential to generate new entrepreneurs, it argues about the need to recycle (capacitation) and the culture of traditional management. It is highlighted that the introduction of sustainable management tools does not mean extra economic costs, instead, it is an opportunity to increase competitiveness, productivity and profits, while incorporating social and environmental responsible practices. While the data collected is possible to suggest ways to introduce sustainable management tools in the praxis of the researched habitats. Is is important to be aware that incubators and technological parks are fertile terrain, because they are working closed to universities and research centers. This can facilitate the construction of partnership which can nininizes risks of new innovative process in the base of new entrepreneurships.